The Effect Of The Implementation Of Customer Relationship Management, Increasing Experiental Marketing, And The Application Of Religiosity On The Loyalty Of Diversification Savings Customers Of Bank Nagari Syariah Olo Padang Branch - Darman, Darman; Rosa, Devi Triana (Adpebi Science Series, 2024)
This study aims to determine the influence of the Implementation of Customer Relationship Management, Increasing Experiental Marketing, and the Application of Religiosity on the Loyalty of Bank Nagari Syariah Diversification Savings Account Olo Padang Branch. The sampling technique uses a sampling technique, using the Slovin formula so that a sample of 97 people was obtained. The Customer Relationship Management variable (X1) with a tcal value of 2.365 and a value of (Significant = 0.016 <0.05) with (df= n-k, then n= number of respondents, k= number of research variables) df= 97-4=93, then a table of 1.661 was obtained. This means that H1 is accepted, so it can be concluded that Customer Relationship Management has a positive and significant effect on the customer loyalty of Bank Nagari Olo Padang Branch. The Experiental Marketing variable (X2) with a tcal value of 1.890 and a value of (Significant = 0.047<0.05) with (df= n-k, then n= number of respondents, k= number of research variables) df= 97-4=97, then a table of 1.661 was obtained. This means that H2 is accepted, so it can be concluded that Expeiental Marketing has a positive and significant effect on Customer Loyalty of Bank Nagari Syariah Olo Padang Branch. The Religiosity variable (X3) with a tcal value of 2.258 and a value of (Significant = 0.011 <0.05) with (df= n-k, then n = number of respondents, k = number of research variables) df= 97-4=93, then a table of 1.661 was obtained. This means that H3 is accepted, so it can be concluded that Customer Relationship Management has a positive and significant effect on the Customer Loyalty of Bank Nagari Syariah Olo Padang Branch. The F test is known that the value offcal is 5.751 >from the ftable 2.70 and the significance of f = 0.006 < 0.05, meaning that H4 is accepted. It can be said that the Implementation of Customer Relationship Management, Increasing Experiental Marketing, and the Implementation of Religiosity have a positive and significant effect on the Customer Loyalty of Bank Nagari Syariah Diversified Savings Account Olo Padang Branch. This means that the variables of Customer Relationship Management Implementation, Increasing Experiental Marketing, and Implementation of Religiosity can explain the variable of Customer Loyalty of Bank Nagari Syariah Diversification Savings Bank Olo Padang Branch, by 22.4%. The remaining 77.6% was explained by other variables that were not observed in this study.